-10(a+3)+6a=

Simple and best practice solution for -10(a+3)+6a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(a+3)+6a= equation:


Simplifying
-10(a + 3) + 6a = 0

Reorder the terms:
-10(3 + a) + 6a = 0
(3 * -10 + a * -10) + 6a = 0
(-30 + -10a) + 6a = 0

Combine like terms: -10a + 6a = -4a
-30 + -4a = 0

Solving
-30 + -4a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + -4a = 0 + 30

Combine like terms: -30 + 30 = 0
0 + -4a = 0 + 30
-4a = 0 + 30

Combine like terms: 0 + 30 = 30
-4a = 30

Divide each side by '-4'.
a = -7.5

Simplifying
a = -7.5

See similar equations:

| 7c-15-5c+42= | | 12-2c=2whatisc | | 6(n+3)+2n= | | -7(y-11)= | | -5+6c-5c= | | 5(1+3x)=125 | | -3n+8+8n= | | 40h+25k+35= | | -8c+c= | | -3a+11a= | | 305=0.15x+16y | | 9=2y-(2y-9) | | 2(x+15)=16 | | 305=0.15y+16x | | (7x+3y)-(2x-3y)= | | 10m-8m= | | -12-15x=3 | | 6(6+3x)=54 | | 24x+24y= | | -4(r-4s-9t)= | | 19.6t^2-14t+8=0 | | 45(-11-32)=c | | x-5=2(23.5)+12 | | -8(2t+6)=-112 | | 16=y+2 | | 2(4x-2)=7x | | 8(s-10)=-124 | | 16a^2-24a+1=0 | | -4+2x=-8+16 | | 4(10+7x)=152 | | 2secx+8sinx=0 | | 10x^2+5x+11=9x^2-x+2 |

Equations solver categories